An overview of the optically detected magnetic-state-selected cesium beam clock - Chen, Sifei; Liu, Chang; Fan, Lifeng; Liu, Chen; Li, Yuanhao; Xu, Shaohang; Li, Chaojie; Wang, Yanhui (Frontiers in Physics, 2022)
Among all kinds of compact cesium beam clocks, the optically detected magnetic-state-selected cesium beam clock (OMCC) combines the advantages of the magnetic state selecting scheme and fluorescence detecting method. This paper presents an overview of the OMCC. Technical issues, noise sources, frequency shifts and improvements of OMCC are reviewed. Finally, the frequency stability of five OMCC is given, which is better than the stability of the high-performance version of Microsemi 5071A.